PENINGKATAN PROSES PEMBELAJARAN MENULIS PROPOSAL PADA SISWA KELAS XI SMA MUHAMMADIYAH 1 KARANGANYAR MELALUI NUMBERED HEAD TOGETHER - Muhammad Zikri Wiguna (Jurnal Metamorfosa, 2020)
The aims of this study are to improve: the quality of students’ learning in writing proposal at Grades XI SMA Muhammadiyah 1 Karanganyar through implementing Numbered Head Together model. This study is a classroom action research. The research was conducted in three cycles. Each consisted of planning, implementation, observation, and reflection. The Subjects of this research were the students of ICT Grades XI SMA Muhammadiyah I Karanganyar and an Indonesian Language teacher. The data sources were collected from the teacher, the students, the activities of teaching learning proces, and the documents. The techniques of collecting data were observation, interview, and test. The data were analyzed by using critical analysis and descriptive comparative analysis. The results showed that the use of model learning can improve the quality of process learning to write proposals. Based on the analysis of data, the quality of the learning process of writing a proposal covers activeness, attention, and independence of students achieving a total score of 186 on the first cycle with 7.2 of average. In the second cycle reached 267 with an average of 10.27, and the third cycle reached 295 with an average of 11.27. Abstrak Tujuan dari penelitian ini adalah untuk meningkatkan: kualitas pembelajaran siswa dalam menulis proposal di Kelas XI SMA Muhammadiyah 1 Karanganyar melalui penerapan model Numbered Head Together. Penelitian ini adalah penelitian tindakan kelas. Penelitian ini dilakukan dalam tiga siklus. Masing-masing terdiri dari perencanaan, implementasi, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas X TIK SMA Muhammadiyah I Karanganyar dan guru Bahasa Indonesia. Sumber data dikumpulkan dari guru, siswa, kegiatan proses belajar mengajar, dan dokumen. Teknik pengumpulan data adalah observasi, wawancara, dan tes. Data dianalisis dengan menggunakan analisis kritis dan analisis komparatif deskriptif. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran dapat meningkatkan kualitas proses pembelajaran menulis proposal. Berdasarkan analisis data, kualitas proses pembelajaran menulis proposal meliputi keaktifan, perhatian, dan kemandirian siswa mencapai skor total 186 pada siklus pertama dengan rata-rata 7,2. Pada siklus kedua mencapai 267 dengan rata-rata 10,27, dan siklus ketiga mencapai 295 dengan rata-rata 11,27. Kata Kunci : Menulis Proposal, Kualitas Pembelajaran, Numbered Head Together